Comparing dual antiplatelet therapy strategies post-acute coronary syndrome: network meta-analysis. (3rd October 2022) - Turgeon, R; Hong, C; Wang, E H Z; Wong, G C; Ellis, U
Abstract: Background: Various approaches to dual antiplatelet therapy (DAPT) management exist to balance thrombotic and bleeding risks following acute coronary syndrome (ACS). Purpose: The aim of this study was to compare and rank different DAPT management strategies in patients with ACS with or without percutaneous coronary interventions. Methods: We conducted a systematic review with network meta-analysis of randomized controlled trials comparing DAPT strategies in patients with ACS using MEDLINE, Embase, and CENTRAL (2007-July 2021). The primary outcome was major adverse cardiovascular events (MACE). Secondary outcomes included all-cause death and major bleeding. We performed Bayesian network meta-analyses to compare all interventions simultaneously using the Markov-chain Monte Carlo method, conducted under the assumption of transitivity. We generated odds ratios (ORs) with 95% credible intervals (CrI) from the medians and 2.5th and 97.5th percentiles of the posterior distributions using a hierarchical Bayesian framework, using a random-effects model with informative priors for between-study heterogeneity based on pharmacological interventions with semi-objective outcomes (MACE or bleeding) or death. To rank interventions for each outcome, we calculated the mean surface under the cumulative ranking (SUCRA) curve. Results: From 5941 articles, we included 24 trials (89, 620 patients). Both clopidogrel- and ticagrelor-based DAPT increased MACE compared with pharmacogenomics-guided P2Y12 inhibitor selection (odds ratio [OR] 1.37, 95% credible interval [CrI] 1.08–1.74 and 1.35, 1.05–1.79, respectively) and empiric P2Y12 inhibitor de-escalation (OR 1.53, 95%CrI 1.00–2.30 and 1.51, 1.00–2.27, respectively). Compared with short-duration DAPT, standard DAPT duration with all P2Y12 inhibitors (clopidogrel, prasugrel, ticagrelor) and pharmacogenomics-guided P2Y12 inhibitor selection increased major bleeding. Ticagrelor-based DAPT increased major bleeding compared with platelet function testing-guided DAPT (OR 1.60, 95%CrI 1.00–2.55). Empiric P2Y12 inhibitor de-escalation ranked best for MACE (SUCRA 0.89), whereas short-duration DAPT ranked best for death (SUCRA 0.89) and major bleeding (SUCRA 0.93). Conclusions: In patients with ACS, empiric P2Y12 inhibitor de-escalation was most efficacious whereas short-duration DAPT was the safest compared to other DAPT strategies. Funding Acknowledgement: Type of funding sources: None.